Avaliação da viabilidade da implementação da tecnologia de gelificação na produção de insumos para diagnóstico - Costa, Maykon Luiz Nascimento (2017)
Among Latin American countries, Brazil is the one that receives more blood donations in volume, reaching up to 3.5 million blood bags in the public blood donation network annually. In order to enable transfusions and processing of blood-derived products, it is mandatory to test the blood against pathologic agents. In association with the Oswaldo Cruz Foundation (FIOCRUZ), the Molecular Biology Institute of Paraná (IBMP) supplies the kit NAT for the detection of the human immunodeficiency, hepatitis B and C viruses (HIV, HBV and HCV) to the Brazilian public blood donation network. Aiming at the implementation of improvements and the introduction of new technologies to its processes, the Institute acquired a license to use the gelification technique in the production of diagnostic kits. The gelification technique proposes the stabilization of biomolecules without harming their functionality, while reducing production costs and allowing the products to be stored and transported at room temperature. It is a key aspect to simplify the logistics chain used to distribute the kit, allowing it to reach World`s remote areas. However, there is still a lack of published studies evaluating financial aspects of the implementation of this technique in the industry. It is worth emphasizing the cost to conduct field experiments of this kind of implementation. One alternative for such an evaluation is by the use of process computer simulation. Simulation tools could be used to analyze different scenarios, providing valuable information for process improvement and decision-making. In this work, the impacts of the gelification technique implementation in the direct production cost of reagents for diagnostic were evaluated using discrete simulation with FlexSim®. Data obtained from sixteen simulated scenarios deploying gelification were compared with historic records of the production of reagents for diagnosis using the conventional process at IBMP. Six of the sixteen evaluated scenarios satisfied the restrictions imposed by the process and all of them indicated a reduction of direct production costs, varying from 3.73% to 5.41% when compared to current conditions. The cost reduction is mainly associated to lower expenses with raw materials, representing savings of up to 4.1% and to the reduction in the number of operators needed. Additionally, results indicate that the implementation of the new technology leads to a better use of the physical structure of the production facility without saturating processing lines. Therefore, based on simulation models, this work shows that the employment of the gelification technology in the manufacturing process of diagnostic reagents at IBMP is viable in terms of direct production costs.